Penguatan Budaya Literasi Digital Islami Melalui Edukasi Pemanfaatan Media Sosial di Kelurahan Cilaku - Yuniar, Euis Ismayati; Jalaludin, Ega; Aeni, Gita Kurotul; Hesti, Neng; Pratama, Yofie (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2026)
The lack of Islamic digital literacy not only increases the risk of spreading hoaxes and violating communication ethics but also results in a lack of understanding of how to utilize digital media for social and economic needs. The objective of this community service focuses on strengthening the culture of Islamic digital literacy and improving the quality of social media utilization for the advancement of Cilaku Village residents, using the Asset-Based Community Development (ABCD) approach, namely the stages of "Discovery, Dream, Design, Define, and Destiny." Through direct training, interactive discussions, socialization on the use of digital attack application technology, and practice in creating social media accounts for MSMEs for social and economic needs. This program results in increasing the digital competence of the community while encouraging the formation of a productive, responsible, and moral digital culture. The contribution of this activity lies in the development of a model for strengthening Islamic digital literacy that not only instills social media ethics based on Islamic values but also improves the community's ability to utilize digital technology for social and economic needs.